STEAP1 is overexpressed in cancers: A promising therapeutic target - Moreaux, Jérôme; Hose, Dirk (Biochemical and biophysical research communications, 2012)
The six-transmembrane epithelial antigen of prostate (STEAP) protein was identified in advanced prostate cancer and is up-regulated in multiple cancer cell lines, including prostate, bladder, colon, ovarian, and Ewing sarcoma. STEAP1 was described as a suitable antigen for T-cell-based or antibody-based immunotherapy. We have investigated the expression of STEAP1 in 40 human tumor types - brain, epithelial, lymphoid - and in their normal tissue counterparts using publicly available gene expression data, including the Oncomine Cancer Microarray database. STEAP1 was found significantly overexpressed in 11 cancers. In addition, high STEAP1 expression was associated with poor overall survival in colorectal cancer, diffuse large B cell lymphoma, acute myeloid leukemia and multiple myeloma. Taken together, these data suggest that STEAP1 is a potential therapeutic target for T-cell based immunotherapy or antibody therapy in a large panel of cancers.